The Implementation of Total Physical Response (TPR) Method in English Learning For Fourth Grade Students at SDN Pesawahan 1 - Hanifah; Zainuddin; Feri Ferdiyanto (LPPM Universitas PGRI Semarang, 2026)
This study aims to investigate the implementation of the Total Physical Response (TPR) method in English learning at SDN Pesawahan 1, explore students' responses to the method, and identify challenges encountered during its implementation. This study used qualitative methods with a descriptive design. Participants consisted of one English teacher and 20 fourth-grade students at SDN Pesawahan 1, located in Pesawahan Village, Tiris District, Probolinggo Regency. Data were collected through classroom observations, interviews, and documentation. Data were analyzed using data reduction, data presentation, and conclusion drawing. The findings indicate that the implementation of the TPR method was carried out through several stages, including providing verbal instructions, demonstrations of movements, students' physical responses, and repetition activities. The use of TPR created a more active and interactive classroom atmosphere. Most students responded positively to the method. They felt more enthusiastic, motivated, and interested in learning English through physical movements and games. This method also helped students understand and memorize English vocabulary more easily. However, several challenges were encountered during implementation, such as classroom management difficulties, differences in student comprehension, limited vocabulary mastery, and limited learning time. In conclusion, the Total Physical Response (TPR) method is effective in increasing student participation, motivation, and vocabulary comprehension in English learning at the elementary school level. Therefore, this method can be considered an alternative teaching strategy to create a more enjoyable and interactive English learning environment for early childhood students.